1999
DOI: 10.1038/sj.onc.1202962
|View full text |Cite
|
Sign up to set email alerts
|

The role of wild-type p53 in the differentiation of primary hemopoietic and muscle cells

Abstract: Experiments previously performed on 32D and C2C12 cell lines indicated that wild type p53 (wtp53) protein has a role in granulocyte and myotube di erentiation. Since these are immortal cells, we asked whether the inhibition of di erentiation induced by the expression of dominantnegative p53 (dnp53) proteins was dependent on the immortalization-determined microenvironment. Thus, we evaluated the e ects produced by interfering with the endogenous p53 gene in murine primary hemopoietic and muscle cells. Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
5
28
0
Order By: Relevance
“…Unstimulated, proliferating cells were chosen as a reference point in these experiments. As expected, proliferating C2-PG 13 CAT cells had a basal chloramphenicol acetyltransferase (CAT) activity comparable to the C2-MG 15 CAT control cells (data not shown). Absence of CAT activity was also found in DAA cells, while a fourfold induction of activity was consistently found in the differentiating population ( Figure 1B).…”
Section: Dear Editormentioning
confidence: 65%
See 4 more Smart Citations
“…Unstimulated, proliferating cells were chosen as a reference point in these experiments. As expected, proliferating C2-PG 13 CAT cells had a basal chloramphenicol acetyltransferase (CAT) activity comparable to the C2-MG 15 CAT control cells (data not shown). Absence of CAT activity was also found in DAA cells, while a fourfold induction of activity was consistently found in the differentiating population ( Figure 1B).…”
Section: Dear Editormentioning
confidence: 65%
“…PG 13 GFP-transduced C2C12 cells (C2-PG 13 GFP) were selected and checked for response to p53 activation by Adriamycin (ADR)-induced DNA damage. In the presence of differentiation promoting medium, the appearance of green fluorescence in C2-PG 13 GFP cells began after 24 h and reached its maximum after 48 ± 72 h ( Figure 1A). Morphological analysis of C2-PG 13 GFP cells showed that GFP was present in all the differentiated C2C12 cells.…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations